Talent identification and women's soccer: An Australian experience - Hoare, D. G.; Warr, C. R. (Journal of Sports Sciences, 2000)
This study used a quasi-applied research model to identify and develop potentially talented female soccer players. Athletes aged 15-19 years with a background in team ball sports or athletics were targeted for recruitment using advertisements and promotions through various media. Interested athletes attended a 2-day programme of testing, which included assessment of anthropometric, physiological and skill attributes. A combination of factors was used in the final selection of 17 athletes to take part in a 12-month talent development programme. A pre-season programme of five training sessions per week was conducted for 2 months. This programme focused on enabling the players to acquire the necessary ball and game skills to perform competitively in a short time. The squad competed as a team in the reserve grade competition of an Australian state league. At the conclusion of the 25-game season, 10 players were selected for zone teams with two players progressing to state team selection within 6 months. The project demonstrates that it is possible to select potential female soccer players based on anthropometric, physiological and skill attributes.Selection procedures could be enhanced through the development of objective assessment tools that measure tactical and technical competence. Programmes such as this can offer an additional avenue of player recruitment in support of existing procedures.